ANALISIS SISTEM KLAIM JAMINAN HARI TUA DAN PERHITUNGANNYA PADA BPJS KETENAGAKERJAAN CABANG MAGELANG - Indira, Adelia Laksmi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study was conducted with the aim of finding out the description of the Old Age Security (JHT) claim system and its calculations for workers who have become Old Age Security (JHT) participants at BPJS Ketenagakerjaan Magelang Branch. The results of this study indicate that the implementation of the old age security claim system at BPJS Ketenagakerjaan Magelang Branch is generally not in accordance with existing regulations. This is based on the fact that participants do not attach a Certificate of Retirement or a Certificate of No Longer Working when making a claim. The use of the old age security claim system is less effective because many participants still make claims only at branch offices, even though in addition to going through branch offices, participants can make claims online. For the calculation of the old age security balance, the benefits obtained will be better if claimed at an old age than at a young age, according to the benefits of JHT itself which are provided for the participant's old age, Income from interest on the development of the old age security balance makes the benefits of old age security more pronounced when making a claim in old age, interest on the development of the balance will increase the participant's balance even though the participant no longer pays contributions.